Fatores prognósticos e mortalidade por infecção relacionada à assistência à saúde em hospital de ensino na Amazônia ocidental brasileira - Faro, Andre Ricardo Maia da Costa de [UNIFESP] (2018)
Objective: Analyze hospital mortality and investigate the deaths associated with healthcareassociated infection (HAI) in a teaching hospital. Method: Databases of the Hospital Information System and System on Mortality of the Unified Health System and the records of the Epidemiological Surveillance Service of the institution of the deaths occurred in the period from January 1st to December 31, 2016. Results: The results of this research allowed the elaboration of three papers with a focus on mortality and emphasis on HAI. The first paper was a crosssectional, exploratory and census study. Among the 634 deaths at the institution in the selected period, the majority of the patients were male (56.9%), with a mean age of 63.03 (SD = 17.02) years, predominantly brown (68.9%), marital status declared single (32.2%), with an average time of hospitalization of 20.76 (SD = 55.09) days, the main underlying cause of death was neoplasms (45.4%) and infectious diseases and parasitic as the main immediate causes of death (28.9%).The second was a descriptive and analytical study of 422 patients over 48 hours of hospitalization who died in the study period. The majority of the patients were male (59.0%), with a mean age of 63.75 (SD= 17.18) years, nonwhite race/color (75.1%), without companion (53.8%), mean of hospital stay of 17.7 (SD=13.80) days from their homes (54.7%). The frequence of HAI was 23.5% and of these, 55.6% were contributing to death. After adjusting the variables by logistic regression using the likelihood ratio method, the use of corticosteroids (OR 1.94 95% CI 1.073.54, p=0.04), bladder catheter (OR 2.67 95% CI 1.274.83, p=0.01) and lenght of stay over 7 days (OR 7.89 95% CI 2.9621.03, p<0.001). Infection present at admission showed inverse association (OR 0.12 95% CI 0.060.23, p<0.001). The third, was a retrospective cohort study of 99 patients with HAI who died during the observation period. The probability of surviving at the first seven days after diagnosis of HAI was 54.5%. The median survival time after the diagnosis of HAI was 9 days. The risk was higher among female patients (52.2%) with age above 65 years (48.1%). They were associated with the risk of death: use of invasive devices (mechanical ventilation, orotracheal tube, tracheostomy, central venous catheter and bladder catheter) and ICU admission. Conclusion: The occurrence of HAI requires special attention because they constitute a serious public health problem due to its high morbidity and mortality. It reinforces the need to improve the measures of prevention and control of the transmission of this type of aggravation. However, besides the findings presented in this thesis find support in the literature on this subject and contribute with information in the area of health, it is pointed out the need for further investigations in order to know the severity of these infections, as well as the involved etiological agents.